2010
DOI: 10.1111/j.1756-5391.2010.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Revised STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA): Extending the CONSORT Statement

Abstract: The STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) were published in five journals in 2001 and 2002. These guidelines, in the form of a checklist and explanations for use by authors and journal editors, were designed to improve reporting of acupuncture trials, particularly the interventions, thereby facilitating their interpretation and replication. Subsequent reviews of the application and impact of STRICTA have highlighted the value of STRICTA as well as scope for improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
178
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(186 citation statements)
references
References 55 publications
0
178
0
Order By: Relevance
“…Written informed consent was obtained from all participants prior to inclusion in the study. The study is reported in compliance with the CONSORT statement (www.consort-statement.org) [27] as well as STRICTA (Standards for Reporting Interventions in Clinical Trials of Acupuncture) [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from all participants prior to inclusion in the study. The study is reported in compliance with the CONSORT statement (www.consort-statement.org) [27] as well as STRICTA (Standards for Reporting Interventions in Clinical Trials of Acupuncture) [28]. …”
Section: Methodsmentioning
confidence: 99%
“…The CONSORT statement has been further revised and is published as the CONSORT 2010 statement. Combined with the CONSORT statement, the acupuncture-specific Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA) were designed to help authors fully report the acupuncture intervention in clinical trials [15,16]. The combination of both tools helps us evaluate the completeness and transparency of RCTs reports on acupuncture for stroke rehabilitation according to their items.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of electrical stimulation was between 2 hertz (Hz) and 100 Hz and was applied for a range of time between 20 and 60 minutes. Details of EA treatments are displayed in Table 2, referring to the Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICA) [57]. …”
Section: Resultsmentioning
confidence: 99%